The impact of social support on the quality of life of the elderly from rural areas - Despotovic, Mile Lj (Medicinski časopis, 2020)
Summary Aim: The aim of this paper is to determinate whether social support affects the quality of life of elderly people from rural areas and to examine whether there are differences between the quality of life of the elderly living in the family and those who live alone. Methods: An epidemiological observation study was conducted, according to the type of cross section study. The sample consisted of 110 subjects. To measure social support, Berlin Social Support scale was used, and to assess quality of life 10-points Likert scale was used . Normal K-K Plot and histogram graphs were used to test the agreement of the sample distributions with the normal distribution, as well as the tests: Kolmogorov-Smirnov and Shapiro-Vilk. The Kruskal Vallis and Vilkisson test sum scores were used to test for differences in quality of life score and overall social support. Results: All parameters of social support affect life satisfaction. These differences are statistically significant (p <0.05), which was also shown by Spirman’s correlation. Respondents who rated the relationships with housemates as excellent had the highest average grade of satisfaction with life (7.38), while those who rated these relationships as horrible had the lowest average grade of satisfaction with life (1.57). Frequent contacts with close relatives and friends on a weekly basis correlate with a higher degree of life satisfaction. Conclusion: It can be concluded that the index of total social support and all of its subgroups correlate with subjective life satisfaction of elders. Key words: social support, quality of life, elderly